Heart rate variability with orhtoclinostatic load in patients with neuroreflex syncopal states - O. V. Grebenyuk; N. G. Katayeva; N. S. Novikova; M. V. Svetlic (Бюллетень сибирской медицины, 2010)
The initial vegetative tonus and vegetative reactivity were studied in patients with neuroreflectory syncopal states (NSS) during passive orthostatic testing in the orthostatic and clinical phases. The variability of the heart rhythm was estimated on the Neiron-spektr device. During the orthostatic testing, the insufficient activity of the sympathetic part of the nervous system in NSS patients was observed compared to the control group. During the clinostatic testing, the indices of NSS patients approached the normal values.